Hubungan antara Kualitas Pertemanan dengan Identitas Vokasional pada Siswa SMAN - Ilmi, Nurul; Rifani, Rohmah; Ansar, Wilda (Universitas Negeri Makassar, 2025)
Identity confusion is very vulnerable among teenagers. The inability of adolescents to resolve conflicts has an impact on confusion about their goals, talents, and abilities in determining their future careers. This study aims to determine the relationship between the quality of friendship and students' vocational identity. The respondents were 171 students at SMA Negeri 8 Bulukumba class XII which was obtained through purposive sampling techniques. Data was collected through questionnaires using a friendship quality scale and a vocational identity scale. The results of Pearson product moment correlation analysis showed the value of the correlation coefficient between the quality of friendship and the achievement identity status, which was r = 0.256 and p = 0.002 (significant). This means that there is a positive correlation between the quality of friendship and vocational identity in the status of achievement and not correlated with the status of moratorium, foreclosure, and diffusion identity. So, the better the quality of the friendship you have, the more your achievement identity will also increase. The implication of this study is necessary to make efforts to maintain the quality of friendships so that they continue to contribute positively in exploring careers and forming commitments to students in various alternative vocational fields.